FULL MOUTH REHABILITATION IN CHILDREN DONE UNDER GENERAL ANESTHESIA IN A DENTAL COLLEGE - Hinaz, Nashwah; Gurunathan, Deepa; V, Ashok (International Journal of Psychosocial Rehabilitation, 2020)
Oral health is an essential component of total health and well-being. For most children, dental treatment under normal dental settings is difficult. This is due to the multiple treatments that are required which can take longer hours and less corporation. Children are highly anxious and uncooperative as well. Hence oral rehabilitation under general anesthesia is highly preferred to reduce stress and increase comfort. The aim of this study is to analyze full mouth rehabilitation of children under General anesthesia in a dental college over a period of one year. Data was collected from June 2019 to March 2020 from Saveetha dental College, Chennai. Data collected was tabulated in Excel and SPSS analysis was performed to obtain the results. A total of 84 patients reported to the dental clinic. The mean age of the participants is 4.23 years. Based on gender distribution, males were 46.2% and females contributed to 53.51%. More number of pulp therapy and crown placement was seen in children aged five years. Restorations were more common in the two-year age group. Maximum number of extractions were done for children aged eight years. Within the limits of this study, full mouth restoration was done for children under general anesthesia and the preference for treatments under general anesthesia was more for the patients in the age group 3 to 4 years.